Demonstration of pulmonary vein exit block following pulmonary vein isolation: A novel use for adenosine. (18th October 2018) - Wynn, Gareth; Gupta, Dhiraj; Maille, Baptiste; Snowdon, Richard; Waktare, Johan; Todd, Derick; Hall, Mark; Mahida, Saagar; Modi, Simon
Abstract: Introduction: Demonstration of exit block after pulmonary vein isolation (PVI) is the cornerstone of ablation for atrial fibrillation (AF). It requires the demonstration of local pulmonary vein (PV) capture and absence of conduction to the atrium but is often challenging due to the inability to see local paced PV‐evoked potentials. We retrospectively examined the ability of adenosine to augment this technique during CARTO‐based radiofrequency ablation procedures. Methods: Retrospective analysis of evoked PV potentials during adenosine administration while testing for PV exit block at a single UK center. Results: One hundred and twenty‐nine PVs in 33 patients were isolated using radiofrequency energy to demonstrate entry block. Of those, the pacing of 24 veins under baseline conditions did not clearly demonstrate local PV‐evoked potentials sufficient to be sure that the local vein was truly captured and dissociated from the atrium. Adenosine was administered in 19 of these, with 10 of 19 (52.6%) veins then demonstrating clear local PV‐evoked potentials transiently during adenosine administration, sufficient to allow assessment of definite exit block. Conclusion: Adenosine administered during PV pacing allows transient visualization of local PV‐evoked potentials after PVI facilitating the clearer demonstration of PV exit block in over 50% veins.